The beggar queen - Alexander, Lloyd (New York : Dutton, 1984)
Chaos reigns in Marienstat as Duke Conrad of Regia, the king's uncle, plots to overthrow the new government of Westmark and bring an end to the reforms instituted by Mickle, now Queen Augusta, Theo, and their companions.
Sequel to: The kestrel.
Notable/Best Books (A.L.A.).
Wilson's Children.
Wilson's Junior High School.
6.9
5-8
Keywords: Fantasy; Fantastic fiction